Kaitan Informed Consent Dengan Prinsip Hak Asasi Manusia Di Era Digital - Gaol, Hotben Marchiano Lumban; Siregar, Rospita Adelina (Jurnal JURISTIC, 2025)
Informed consent is an important principle in protecting individual rights, especially in the context of medicine, research, and is now increasingly relevant in the digital world. In the digital era, the collection, use, and distribution of personal data pose new challenges to the protection of human rights, especially the rights to privacy, freedom of expression, and protection against data misuse. This research is a normative legal research with a statutory approach.Â  This article examines the relationship between Informed consent and human rights principles in the digital era, and provides a critical analysis of its implementation in current digital policies and practices